Answer:
-2 I believe. because the 1st exponent would make it 9, and then you'd remove 2
Step-by-step explanation:
I hope this is correct and helpful, I tried my best! <3
Answer:
4/3
Step-by-step explanation:
Answer:
f(-3) = 16
Step-by-step explanation:
Given:
f(x) = 2x² + x + 1
Required:
f(-3)
Solution:
Substitute x = -3 into f(x) = 2x² + x + 1
f(-3) = 2(-3)² + (-3) + 1
f(-3) = 2*9 - 3 + 1
f(-3) = 18 - 3 + 1
f(-3) = 16
Answer:
3^6
Step-by-step explanation:
3^2 * 3^4
You add the exponents together.
The answer is 17 and 19/25